A brief synopsis on scalp melanoma. Issue 4 (8th July 2020) - Saaiq, Muhammad; Zalaudek, Iris; Rao, Babar; Lee, Young; Rudnicka, Lidia; Czuwara, Joanna; Giuffrida, Roberta; Wollina, Uwe; Jafferany, Mohammad; Lotti, Torello; Grabbe, Stephan; Goldust, Mohamad
Abstract: Melanoma constitutes one of the most sinister and troublesome malignancies encountered by humanity. Generally, the diagnosis of advanced melanoma connotes a grave prognosis, prompting a sense of looming threat of death, however, the early‐stage detected disease responds well to robust treatment resulting in reasonable survivorship. Scalp melanomas are even more troublesome, because they typically exhibit more aggressive biologic behavior and are often diagnosed at a late stage. This review tries to comprehensively highlight the various diagnostic, therapeutic, and outcome aspects of scalp melanomas. The literature research includes peer‐reviewed articles (clinical trials or scientific reviews). Studies were identified by searching electronic databases (MEDLINE and PubMed) till May 2020 and reference lists of respective articles. Only articles published in English language were included.